2018
DOI: 10.1111/infa.12238
|View full text |Cite
|
Sign up to set email alerts
|

Push or Carry? Pragmatic Opportunities for Language Development in Strollers versus Backpacks

Abstract: Strollers and backpacks are employed early, frequently and throughout the first year, with parents overwhelmingly using strollers. However, because these transport modalities put infants in different proximities to caregivers, postures, and states of alertness, their use may translate to different opportunities that are of developmental consequence, particularly with regard to language. We used GoPro technology in a within subjects counter-balanced design to measure dyadic vocalizations in strollers and backpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
4
6
0
1
Order By: Relevance
“…The present study revealed that newborn primates can distinguish CT-targeted touch from other types of touch, and that touch may positively impact newborns' emotional and attentional development. Our findings add to a growing body of work in humans suggesting neonatal social touch may broadly support not only infants' healthy physical development, but also their psychological development (Anisfeld et al, 1990;Korja et al, 2018;Mireault et al, 2018;Watt, 1990). The effects of social touch may be far-reaching, potentially impacting attention capture and holding earlier in development than previously reported.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The present study revealed that newborn primates can distinguish CT-targeted touch from other types of touch, and that touch may positively impact newborns' emotional and attentional development. Our findings add to a growing body of work in humans suggesting neonatal social touch may broadly support not only infants' healthy physical development, but also their psychological development (Anisfeld et al, 1990;Korja et al, 2018;Mireault et al, 2018;Watt, 1990). The effects of social touch may be far-reaching, potentially impacting attention capture and holding earlier in development than previously reported.…”
Section: Discussionsupporting
confidence: 62%
“…Another study found that 4-month-old infants who received gentle stroking by parents while observing faces were more likely to learn facial identities compared to a no-touch condition (Della Longa, Gliga, & Garroni, 2019). A recent study compared parent-infant interactions during walks while children were either pushed in strollers or carried in backpacks, in which they were in physical contact with parents (Mireault, Rainville, & Laughlin, 2018). They found that, during babywearing, 7-to 11-month-olds had more dyadic conversations with parents, including more infant vocalizations and more infant-initiated interactions, compared to when infants were in strollers.…”
Section: Touch Facilitates Socialitymentioning
confidence: 99%
“…Among factors that are relevant to consider, the use of seating devices is an important candidate given the potential to make practical recommendations regarding their use. Moving beyond previous work linking seating device use to verbal interactions in controlled settings (Little et al, 2019;Mireault et al, 2018), our goal in the present studies is to examine whether the day-to-day use of these devices is associated with infants' language exposure. In Study 1, we examined links between device use and concurrent exposure to adult words (within-child).…”
Section: Infant Seating Device Use and Language Exposurementioning
confidence: 99%
“…Anisfeld et al () conducted a randomized control study on infant carrying among high‐risk mothers and found a robust effect for infants who were worn in infant carriers compared to mothers who carried their infants in bucket seats as having a greater likelihood of a secure attachment style at 13 months (Anisfeld et al, ). Most recently, infant vocalizations, dyadic conversations, and infant‐imitated speech were heightened in dyads that used infant carriers rather than strollers to transport their 7‐ to 11‐month old infants (Mireault, Rainville, & Laughlin, ). Although studies on infant carrying or babywearing are sparse, they suggest that there may be some benefit to prolonged infant contact to the mother and infant relationship, even without direct skin‐to‐skin contact.…”
Section: Early Physical Contactmentioning
confidence: 99%